The Content of the 14 Metals in Cancellous and Cortical Bone of the Hip Joint Affected by Osteoarthritis - Zioła-Frankowska, Anetta (Biomed Res Int, 2015)
The aim of the study was to determine the content of particular elements Ca, Mg, P, Na, K, Zn, Cu, Fe, Mo, Cr, Ni, Ba, Sr, and Pb in the proximal femur bone tissue (cancellous and cortical bone) of 96 patients undergoing total hip replacement for osteoarthritis using ICP-AES and FAAS analytical techniques. The interdependencies among these elements and their correlations depended on factors including age, gender, place of residence, tobacco consumption, alcohol consumption, exposure to environmental pollution, physical activity, and type of degenerative change which were examined by statistical and chemometric methods. The factors that exerted the greatest influence on the elements in the femoral head and neck were tobacco smoking (higher Cr and Ni content in smokers), alcohol consumption (higher concentrations of Ni, Cu in people who consume alcohol), and gender (higher Cu, Zn, and Ni concentrations in men). The factors influencing Pb accumulation in bone tissue were tobacco, alcohol, gender, and age. In primary and secondary osteoarthritis of the hip, the content and interactions of elements are different (mainly those of Fe and Pb). There were no significant differences in the concentrations of elements in the femoral head and neck that could be attributed to residence or physical activity.